PA01.37. Safety and efficacy of UNEX capsules in management of ureteric calculi: A prospective, randomised placebo-controlled study - Deshpande, Sarang (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: Urinary stones have occupied a major place in the urological practices. It is one of the most common and painful urologic disorder of the urinary tract. Generally, the age between 20 to 40 years is more prone to it. As it has a high rate of recurrence, it is affecting economy and general health of the people. METHOD: This study was a prospective, placebo controlled, double blind study. The study incorporated a matched pairs design. Each patient has received a single treatment of either the control or investigational product (UNEX). The goal was to enrol approximately 80 patients in order of having 60 patients (30 in each group) to complete the trial and provide data for analysis. RESULT: Total 72 patients were enrolled in the study, out of which 64 patients completed There was extremely significant results obtained in case of urine analysis of patients for infection, bacteriuria and haematuria, at the end of 6 months, value as compared to before treatment value the study, With the treatment with UNEX capsule, significant relief was observed in case of X ray KUB shows that renal calculi disappeared in 18 patients at the end of 6 months out of 32 patients, whereas USG of renal pelvis shows disappearance in 16 patients out of 32, which is extremely significant as compared to before treatment value where 32 patients showed presence of renal calculi. However, in placebo, only three patients out of 32 showed absence of renal calculi at the end of 6 months of treatment. CONCLUSION: Considering the excellent results of the clinical trial, it can be concluded that UNEX is effective in the treatment of Ureteric calculi, without producing any undesirable side effects. No clinically significant adverse reactions were reported or observed, the clinical trial of UNEX, an Ayurvedic preparation, has proved its efficacy and safety in upper ureteric calculi.